2015
DOI: 10.1038/srep14466
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational epigenetic inheritance in humans: DNA methylation changes associated with maternal exposure to lead can be transmitted to the grandchildren

Abstract: We report that the DNA methylation profile of a child’s neonatal whole blood can be significantly influenced by his or her mother’s neonatal blood lead levels (BLL). We recruited 35 mother-infant pairs in Detroit and measured the whole blood lead (Pb) levels and DNA methylation levels at over 450,000 loci from current blood and neonatal blood from both the mother and the child. We found that mothers with high neonatal BLL correlate with altered DNA methylation at 564 loci in their children’s neonatal blood. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 52 publications
2
79
0
2
Order By: Relevance
“…Notably, Sen et al has also reported that maternal Pb exposure induces epigenetic changes in the germ line of their offspring, impacting DNA methylation in the F2 in humans. These results provide evidence that Pb exposure may induce multigenerational epigenomic changes [63].…”
Section: Leadmentioning
confidence: 57%
See 1 more Smart Citation
“…Notably, Sen et al has also reported that maternal Pb exposure induces epigenetic changes in the germ line of their offspring, impacting DNA methylation in the F2 in humans. These results provide evidence that Pb exposure may induce multigenerational epigenomic changes [63].…”
Section: Leadmentioning
confidence: 57%
“…Related, animal models also foster research examining the transgenerational impacts of exposure. As Sen et al demonstrated, maternal Pb exposure may be related to DNA methylation in the blood of their grandchildren (F2), suggesting that Pb impacts the germ line of a developing fetus [63]. However, assessing truly transgenerational effects is unlikely to be feasible in human populations.…”
Section: Contributions Of Animal Models and In Vitro Experimentsmentioning
confidence: 99%
“…Finally, epigenetic changes can be inherited over generations in humans, indicating that if a mother is exposed to a high level of oxygen that induced oxidative stress and resulted in epigenetic changes, thereby up-regulating the GSH system epigenetically, can also be transmitted to the child [35]. This is an adaptive mechanism that prepares the child for future exposure and ensures that its ability to survive is high in the future expected environment.…”
Section: Long Term Adaptation—transcriptional Epigenetic and Genmentioning
confidence: 99%
“…Several researchers have used DBS data to gain more insight into different conditions and disorders. DBSs have been even used to study how the effect of the environment can affect several generations as demonstrated by Sen and colleagues in their work on inheritance of epigenetic changes associated with exposure to lead [58].…”
Section: B Secondary Use Of Patient Data For Genomic Research and Tomentioning
confidence: 99%